Expectancy effects and strength training: Do steroids make a difference? - Maganaris, C.; Collins, D.; Sharp, M. (The Sport Psychologist, 2000)
Summary Expectations regarding performance have been found to relate to actual performance/ behaviors. The authors took this concept a step further by assessing the role of expectations regarding use of anabolic steroids (AS) on subsequent performance. They attempted to address the role cognitive factors play in the effects of AS. What a powerful weapon against drug use if expectancy effects can be demonstrated. On all athletes, training and diet were controlled and baseline data was collected. In phase 1, competitive powerlifters (who had expressed an interest in AS) were administered placebo AS and given false information about the effects of AS use. In phase 2, half of the athletes were told of the placebo thus modifying their expectations. After each 7 day phase, athletes were tested on various lifts. Findings Following phase 1, during which all the athletes were unaware of the placebo, improvements represented a change in performance that would see the athletes move from the National to the International level. Following phase 2, performance of the participants who were made aware of the placebo returned to baseline levels while the group "still in the dark" maintained their enhanced performance level. Upon completion of the study, all participants readily recognized the crucial role expectancy had played on the performance they achieved. Implications While the study did not attempt to argue against the performance benefits of steroids, it provides an argument for the efficacy of other means of performance enhancement. Specifically, the results of the study suggest that benefits can be gained through expectancy effects alone. That is, athletes who thought they were taking steroids that would enhance their strength demonstrated impressive strength gains. A viable avenue for performance enhancement in swimming may be to address and modify expectations. If our swimmers can "believe" that a facet of their training is a key to improving, this research leads us to believe it just might happen. What are your athletes¡¯ expectations about how various aspects of training influence competitive performance? How can we influence these expectations?